Meditation - Srinivasan, Narayanan (Progress in brain research, 2019)
"Meditation has been practiced for many centuries in multiple traditions throughout the world. There is a large classical literature on meditation training and states of consciousness that could be achieved through meditation practice and its putative beneficial effects. While mediation practice is old, scientific studies on meditation are only decades old and has expanded significantly in the past twenty years. The scientific studies on meditation have focused both on changes in brain and mind due to the practice as well as its benefits to those who suffer from mental disorders. The methodologies used to study meditation have also expanded ranging from experience based sampling, behavioral paradigms, questionnaires, eye tracking, electroencephalography and brain imaging. The current volume explores interdisciplinary research on meditation. The papers cover the current status of research on the effects of meditation on brain and cognition using multiple methodologies. The papers also cover research on different types of meditation. The volume would be of great benefit to meditation researchers worldwide and serve as a resource for neuroscientists, psychologists, cognitive scientists, philosophers, clinicians and educators interested in meditation"--Back cover